Childhood cancer survivors' experiences in school re-entry in South Korea: Focusing on academic problems and peer victimization. (August 2016) - Yi, Jaehee; Kim, Min Ah; Hong, Jun Sung; Akter, Jesmin
Abstract: Childhood cancer survivors are confronted with numerous problems when they return to school after the completion of treatment. This study investigates the school re-entry experiences of childhood cancer survivors in South Korea. In-depth qualitative interviews were conducted with 31 childhood cancer survivors who were between 15 and 39 years old and had completed all cancer treatments at the time of the study. Participants reported being excited about school re-entry, but also being fearful and concerned about their academic performance and peer relationships. The participants' school re-entry experiences were mostly impacted by their relationships with their peers and teachers. They expressed having had psychosocial problems related to school re-entry, such as feeling a sense of loss and a lack of social skills. Our study findings emphasize a critical need for supporting childhood cancer survivors, both academically and socially, in their transition to school. Highlights: Childhood cancer survivors are often socially isolated when returning to school. Academic performance matter for successful school reentry. Supports from peers and teachers are important resources. Children and adolescents experiencing cancer need support in transition back to school.